The Invencion of Calabangaa, Camarines Sur dynamics of family, land, and power - Bien, Juliet R. (Musika Jornal, 2011)
This paper is an ethnographic study which documents and analyzes the invencion in the social context of the town of Calabanga, Camarines Sur. The annual performance of the invencion performed in honor of the Holy Cross on the third day of May is supported by an elaborate system of family sponsorship and land ownership rotated among kindred and heirs of its initiators, the Danabar, Reganit, and Barba patriarchs. The ritual practice consists of three indispensable artistic components: the koronasyon, the lagaylay, and the dalit. These three parts honor the Holy Cross through the performance of women who take the roles of Queen Elena and her attendants in elaborate song and dance sequence.